Mosquito Larvae Identification in Water Storage and Assesment of Worker’s Knowledege, Attitudes, and Practices - Adinda Nezma Meidina; Dwi Handayani; Dalilah Dalilah; Gita Dwi Prasasty; Susilawati Susilawati (Gema Lingkungan Kesehatan, 2026)
Vector-borne diseases remain a major public health concern in tropical regions, with dengue fever continuing to be the predominant vector-borne disease in urban Indonesia. Public tourist areas with high human activity may provide favorable breeding sites, making sanitation workers’ roles crucial. This study aimed to identify mosquito breeding characteristics and larval presence in water-holding containers (WHCs) and to describe the knowledge, attitudes, and practices (KAP) of sanitation workers in a historic public open space in an urban setting. A descriptive cross-sectional study using a mixed-methods approach was conducted, combining quantitative entomological surveys with qualitative in-depth interviews. All accessible WHCs at the study site were inspected for larvae, which were collected and morphologically identified, and Aedes larval indices (ABJ/Angka Bebas Jentik, HI, CI) were calculated. Sanitation workers were selected purposively as qualitative informants, and KAP data were analyzed thematically. Seven WHCs were identified, of which two outdoor natural pools (28.57%) were positive for larvae, yielding 13 larvae, all identified as Culex spp., with no Aedes spp. detected. Consequently, Aedes-specific indices showed an ABJ of 100%, HI of 0%, and CI of 0%, indicating a low risk of dengue transmission according to WHO criteria (HI <4% and CI <3%). Sanitation workers demonstrated generally good knowledge, positive attitudes, and routine preventive practices, although understanding of the full 3M Plus concept varied. In conclusion, despite the presence of non-Aedes larvae in outdoor natural containers, the absence of Aedes breeding sites suggests effective dengue vector control supported by routine sanitation practices in the study area.